Application of Learning Objects for Computer Programming-Based Problem Solving - Basuhail, Abdullah Ahmad (Canadian journal of learning and technology, 2020)
This paper presents an approach to implement learning objects for teaching and learning problem-solving techniques based on computer programming. The demonstrated approach exploits computer-based interactive animations and computer graphics. The main feature of this approach is its simplicity for exploring the concepts and structures of the programming that are used to implement a solution for a problem under consideration. The developed learning objects feature the possibility of reusability and adaptability in e-learning settings. Moreover, the learning objects can be utilized as a hands-on experience for the learners of a certain subject matter. The approach applied for the design and implementation of the learning objects for computer programming-based problem solving can be extended to other disciplines of science and technology. As a demonstration of the proposed methodology, we showed an application that utilizes the approach to implement a learning object for solving a well-known statistics and probability problem.